Efbalropendekin Alfa enhances human natural killer cell cytotoxicity against tumor cell lines in vitro - Shehata, Hesham M.; Dogra, Pranay; Gierke, Sarah; Holder, Patrick; Sanjabi, Shomyseh (Frontiers in Immunology, 2024)
IL-15 has shown preclinical activity by enhancing the functional maturation of natural killer (NK) cells. Clinical evaluation of the potential anticancer activity of most cytokines, including IL-15, has been limited by low tolerability and rapid in vivo clearance. Efbalropendekin Alfa (XmAb24306) is a soluble IL15/IL15-receptor alpha heterodimer complex fused to a half-life extended Fc domain (IL15/IL15Rα-Fc), engineered with mutations to reduce IL-15 affinity for CD122. Reduced affinity drives lower potency, leading to prolonged pharmacodynamic response in cynomolgus monkeys. We show that in vitro, human NK cells treated with XmAb24306 demonstrate enhanced cytotoxicity against various tumor cell lines. XmAb24306-treated NK cells also exhibit enhanced killing of 3D colorectal cancer spheroids. Daratumumab (dara), a monoclonal antibody (mAb) that targets CD38 results in antibody-dependent cellular cytotoxicity (ADCC) of both multiple myeloma (MM) cells and NK cells. Addition of XmAb24306 increases dara-mediated NK cell ADCC against various MM cell lines in vitro. Because NK cells express CD38, XmAb24306 increases dara-mediated NK cell fratricide, but overall does not negatively impact the ADCC activity against a MM cell line likely due to increased NK cell activity of the surviving cells. These data show that XmAb24306 increases direct and ADCC-mediated human NK cell cytotoxicity in vitro.